Ion exchange membrane for flow battery as well as preparation method and application of ion exchange membrane
By designing the ion exchange capacity of the ion exchange membrane for flow batteries with a gradient decreasing or gradually decreasing in the electrolyte flow direction in the ion exchange membrane for flow batteries, the problem of low energy efficiency of the existing membrane under the electrolyte reaction speed gradient is solved, and a higher integration is achieved Energy efficiency and performance balance.
Patent Information
- Application Number
- CN202411582305.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-11
AI Technical Summary
The ion exchange capacity of existing ion exchange membranes for flow batteries in the electrolyte flow direction is uniform, and the gradient of the electrolyte reaction speed cannot be effectively utilized, resulting in a low overall energy efficiency of the battery.
Design an ion exchange membrane for liquid flow batteries, which has a gradient decreasing or gradually decreasing ion exchange capacity in the flow direction of the electrolyte. By using resins with different ion exchange capacity in different areas of the membrane reaction area, the changes in the reaction speed of the electrolyte are matched. , thereby optimizing the voltage and Coulomb efficiency of the membrane.
Through the design of ion exchange capacity with decreasing gradients, the overall energy efficiency of the flow battery is improved, the voltage and Coulomb efficiency are balanced, the membrane surface resistance is reduced, and the overall performance of the battery is improved.
Smart Images

Figure CN119419326A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of ion exchange membranes, in particular to an ion exchange membrane for a liquid flow battery and a preparation method and application thereof. The ion exchange membrane is particularly suitable for an ion exchange membrane for a vanadium liquid flow battery. Background Art
[0002] In liquid flow batteries, ion exchange membranes play the role of blocking the active materials of the positive and negative electrodes to prevent cross-mixing, while conducting ions to form a conductive circuit inside the battery. At present, there are two main types of ion exchange membranes for liquid flow batteries: homogeneous membranes and composite membranes. Homogeneous membranes refer to membrane materials whose components are uniform in the membrane surface direction and thickness direction, such as Nafion membranes; composite membranes refer to membrane materials with a certain variation in components in the thickness direction and a multilayer structure, such as Gore's ePTFE reinforced membrane. However, the components of these two membranes are consistent in the membrane surface direction. Therefore, the performance of membrane surface resistance / proton conductivity and ion selectivity at any point on the membrane surface is consistent. But the actual situation is that in the flow battery stack, the speed of the redox reaction of the electrolyte on the electrode gradually decreases along the flow direction of the electrolyte. This is because at the inlet of the electrolyte, the concentration of the active substances in the electrolyte reaction is sufficient. As the active substances in the electrolyte react and flow along the electrode, the concentration of the active substances gradually decreases, and its reaction rate will decrease. This also makes the reaction rate on the membrane surface positively correlated with the reaction rate of the active substances on the electrode surface, that is, it shows a certain regularity along the flow direction of the electrolyte. Therefore, we can make full use of this principle to design and develop ion exchange membranes for flow batteries in a targeted manner, which can improve the comprehensive energy efficiency of ion exchange membranes in flow battery stacks to a certain extent.
[0003] In the ion exchange membrane used in liquid flow batteries, ion exchange capacity (IEC) is a very important indicator. Generally speaking, the larger the IEC value, the more ion exchange groups per unit mass of the ion exchange membrane. At the same membrane thickness, the lower the membrane surface resistance, the higher the voltage efficiency, but the ion selectivity may deteriorate and the coulombic efficiency will decrease. Therefore, combined with the reaction rules of the liquid flow battery electrolyte on the electrode and the membrane, the changes in the ion exchange capacity can be specifically designed on the components of the ion exchange membrane to meet the actual needs of the liquid flow battery and improve the energy efficiency of the liquid flow battery. Summary of the invention
[0004] In order to make up for the deficiencies of the prior art, the technical solution of the present invention is as follows:
[0005] An ion exchange membrane for a liquid flow battery. In a reaction zone of the liquid flow battery, the ion exchange capacity values of ion exchange resins in various regions on the ion exchange membrane decrease gradually or gradually along the flow direction of the electrolyte.
[0006] like Figure 1 As shown, in the flow battery / stack, in order to ensure full utilization of the electrolyte and reduce the occurrence of dead zones, the electrolyte is usually introduced from the bottom to the top, that is, the electrolyte enters the stack from the bottom and flows out of the stack at the top. Therefore, the electrolyte enters the reaction zone of the flow battery from the bottom inlet and is evenly distributed, flowing upward in parallel until the electrolyte outlet at the top. As described in the background introduction, the electrolyte reaction rate decreases from bottom to top. In areas where the electrolyte reaction rate is faster, the proton transmembrane exchange rate is faster, and a relatively large ion exchange capacity is required to support it, so as to reduce the membrane surface resistance and improve the voltage efficiency of the overall membrane; in areas where the electrolyte reaction rate is slower, the proton transmembrane exchange demand is lower, and ion exchange resins with lower ion exchange capacity can be selected for use, and the ion selectivity of the slower reaction rate area can be improved, thereby improving the overall membrane Coulomb efficiency.
[0007] Furthermore, the resins with different ion exchange capacities are of the same type, and the resin type is the ion exchange membrane resin widely used in the field of flow batteries, including cation exchange membrane resins and anion exchange membrane resins, specifically including but not limited to perfluorosulfonic acid resins, sulfonated polyetheretherketone resins, sulfonated polyethersulfone resins, polybenzimidazole ion exchange resins, etc. The value or range of the ion exchange capacity of each resin depends on its own properties and is not constrained here. Here, the same type of resin is selected for different ion exchange capacity regions of the ion exchange membrane, so that the resin molecules in different regions have good compatibility, which can avoid the problem of incompatible joints and ensure the stability of the ion exchange membrane.
[0008] If perfluorosulfonic acid resin is used to prepare the ion exchange membrane of the present invention, the ion exchange capacity range is not limited in theory. The preferred ion exchange capacity range of the present invention is 0.75-1.05 mmol / g;
[0009] If sulfonated polyetheretherketone resin is used to prepare the ion exchange membrane of the present invention, the ion exchange capacity range is not limited in theory. The preferred ion exchange capacity range of the embodiment of the present invention is 1.75-2.24 mmol / g.
[0010] Furthermore, the ion exchange capacity of the ion exchange resin on the ion exchange membrane presents at least three gradient changes along the flow direction of the electrolyte. Theoretically, or from the perspective of limit thinking, the ion exchange capacity can present an infinite number of gradient changes, that is, gradual changes. This is because the electrolyte in some cases ( Figure 2(A) solid line), in the membrane reaction area, the reaction rate decreases gradually from bottom to top. In some cases ( Figure 2 (B) solid line), due to the excessive abundance of reactive substances, the reaction rate (maximum reaction rate) can be kept unchanged in a section of the lower end of the membrane reaction zone. Therefore, there can be a relatively wide ion exchange capacity gradient step in the lower end area.
[0011] However, it is relatively difficult to realize the ion exchange membrane with a gradually decreasing ion exchange capacity parameter in the actual production process, and its model or concept currently only exists at the theoretical level; in the actual preparation process, the preparation method of the ion exchange membrane with a gradually decreasing ion exchange capacity IEC value is relatively easy ( Figure 2 Here, the present invention also provides a method for preparing an ion exchange membrane with a decreasing ion exchange capacity value.
[0012] A method for preparing an ion exchange membrane for a flow battery comprises the following steps:
[0013] (S1) preparing ion exchange resin slurries with different ion exchange capacities using the same solvent;
[0014] (S2) placing the above-mentioned ion exchange resin slurry in the head hopper of the casting machine in order of ion exchange capacity, and simultaneously feeding the materials in parallel through the gap of the hopper mold, and then using a scraper to scrape the resin slurry flat at the set knife belt gap, and then transferring it from the casting machine to the film drying area for drying and film formation, so as to obtain the ion exchange membrane of the present invention.
[0015] In step (S1), the viscosity of the ion exchange resin slurry with different ion exchange capacities should be substantially the same (within a tolerance of ±5%) and there should be no gap between the resin slurries in adjacent silos. This will ensure that the scraper can ensure that the slurry is evenly applied when applying the slurry, so that the thickness of different regions of the prepared ion exchange membrane remains consistent, and that there is no gap or fault in the connecting region of the ion exchange capacity in the ion exchange membrane.
[0016] It is worth noting that in the actual film preparation process, the adjacent areas of IEC cannot be combined with zero transition, that is, during the feeding process of the resin slurry and after the scraper coating, its components will have a certain degree of mutual penetration or overlap, forming a transition zone ( Figure 3 ), the average ion exchange capacity of the transition zone is between the IEC of adjacent regions, that is, IEC n-1 <IEC 过渡 <IEC n In order to ensure that the overall performance of the designed ion exchange membrane is not affected too much, the width of the transition area in the membrane reaction zone should be controlled to be less than 2% of the total membrane width, that is, d 过渡n / L n<2%, the transition zone accounts for a relatively small proportion of the total width, and in practical applications, it only needs to be monitored, and does not need to be considered intensively, and can even be ignored. Therefore, the transition zone is temporarily ignored in subsequent embodiments.
[0017] Another point worth mentioning is that the amount of each resin slurry and the corresponding silo mold seam width and other parameters are not limited, which are directly related to the width of each area after film formation, and the present invention does not limit the width of different IEC areas or the ratio of their width to the total length of the electrolyte in the membrane reaction zone. This is because the reaction rate of the electrolyte in the flow battery on the electrode and membrane surface is related to many factors such as electrolyte concentration, flow rate, temperature, operating current density, and is also related to the type of flow battery (i.e., the type of redox couple), so its accurate range cannot be limited. In addition, in the actual application of flow batteries, it is also necessary to consider the balance between the complexity and cost of the membrane manufacturing process and the performance of the flow battery, and optimize the ion exchange membrane structure suitable for the corresponding flow battery system. Combined with the above content, we can also say that as long as it is used in a flow battery, the ion exchange capacity value of the ion exchange resin in each area decreases or gradually decreases along the flow direction of the electrolyte. The ion exchange membrane should be within the protection scope of the present invention.
[0018] The third purpose of the present invention is to request protection for the application of the ion exchange membrane in liquid flow batteries, which can be applied to all vanadium liquid flow battery systems and theoretically can also be used in other liquid flow battery systems, and can improve the efficiency of liquid flow batteries in vanadium battery systems.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] (1) The present invention provides an ion exchange membrane with a new structural composition, the ion exchange capacity (IEC) of which decreases gradually or gradually along the electrolyte direction in the reaction area of the flow battery membrane. It can be designed specifically according to the reaction characteristics of the flow battery, which helps to improve the comprehensive energy efficiency of the flow battery;
[0021] (2) Compared with the existing method for preparing homogeneous membranes for liquid flow batteries, the method for preparing ion exchange membranes for liquid flow batteries according to the present invention does not significantly increase the preparation cost and process flow. It can be achieved by only making corresponding fine-tuning and modifications to the existing equipment. The prepared membrane has more excellent battery performance and can replace the existing ion exchange membrane in the field of liquid flow battery energy storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a schematic diagram of the reaction area and electrolyte flow direction of the membrane flow battery;
[0023] Figure 2This is a schematic diagram of the setting of the theoretical reaction rate and the actual IEC value of the membrane. A indicates that the reactants at the electrolyte inlet are insufficient; B indicates that the reactants at the electrolyte inlet are sufficient;
[0024] Figure 3 This is a schematic diagram of the setting of IEC values in the reaction zone of the membrane flow battery (IEC1>IEC2>···>IEC n ) and IEC transition zone diagram;
[0025] Figure 4 Schematic diagram of the membrane reaction zone size of the ion exchange membrane prepared in Example 1 used in Experiment 1 (A) and Experiment 2 (B);
[0026] Figure 5 The ion exchange membrane prepared in Example 2 is used in Experiment 3 (C) as a schematic diagram of the membrane reaction zone size;
[0027] Figure 6 This is a schematic diagram of the membrane reaction zone dimensions of the ion exchange membrane prepared in Example 3 used in Experiment 4 (D), Experiment 5 (E) and Experiment 6 (F). DETAILED DESCRIPTION
[0028] In order to better understand the present invention, the content of the present invention is further explained in conjunction with the following examples, but the content of the present invention is not limited to the following examples. The following examples describe in more detail an ion exchange membrane for a flow battery and its preparation method and application in the present invention, and these examples are given in an illustrative manner, but these examples do not limit the scope of the present invention. Unless otherwise specified, the experimental method used in the present invention is a conventional method, and the experimental equipment, materials, reagents, etc. used can be purchased from a chemical company.
[0029] Perfluorosulfonic acid resin (H + Sulfonated polyetheretherketone resins with different IEC values were prepared by sulfonation reaction of polyetheretherketone powder with concentrated sulfuric acid. For details, please refer to: Zhang Qingting et al., Preparation and modification of sulfonated polyetheretherketone membrane for DMFC, New Chemical Materials, 2012, 40(3), 121 or other literature.
[0030] The thickness of the ion exchange membrane was tested by a digital micrometer, and 50 values were measured at different positions for each sample to obtain the average value.
[0031] The test method for the ion exchange capacity of the ion exchange membrane or ion exchange resin is tested in accordance with Section 5.8 of the Energy Industry Standard of the People's Republic of China NB / T 42080-2023 "General Technical Conditions and Test Methods for Ion Conducting Membranes for All-vanadium Liquid Flow Batteries";
[0032] The reduced viscosity of the ion exchange resin slurry for membrane preparation was tested by a plate rheometer (AR-G2, TA, US);
[0033] The present invention uses a typical liquid flow battery, the all-vanadium liquid flow battery, as an example to evaluate the performance of the ion exchange membrane liquid flow battery. The performance test conditions of the all-vanadium liquid flow energy storage battery with an ion exchange membrane are: at a current density of 160 mA / cm 2 The charge and discharge experiments were carried out under the following conditions: charging to 1.55V and discharging to 1.00V. The graphite carbon felt produced by Liaoyang Jingu Carbon Materials Co., Ltd. was used as the reaction electrode. The effective working size of the electrode was 60cm×80cm. The positive and negative electrolytes were VO 2+ / VO2 + and V 2+ / V 3+ of sulfuric acid solution, the battery operating temperature is 37°C.
[0034] Example 1
[0035] (S1) perfluorosulfonic acid resin (H) with ion exchange capacities of 0.75 mmol / g, 0.89 mmol / g and 1.05 mmol / g respectively + Type) were dissolved in N, N-dimethylformamide (DMF) to prepare membrane slurries A1, B1 and C1, whose reduced viscosities were 12.5 mPa·s, 12.8 mPa·s and 12.7 mPa·s, respectively;
[0036] (S2) A1, B1 and C1 slurries are placed in turn at the material bins of the casting machine head, the knife-band gap is set to 0.36 mm, and after the resin slurry is scraped flat, it is transferred from the casting machine to the film drying area for drying and film formation, thereby obtaining an ion exchange membrane with a thickness of 48 μm prepared in Example 1. The total effective membrane width is 98 cm, and the widths of the regions with ion exchange capacities of 0.75 mmol / g, 0.89 mmol / g and 1.05 mmol / g are 34 cm, 28 cm and 36 cm, respectively.
[0037] Example 2
[0038] The knife-band gap was set to 0.57 mm, and other conditions were kept the same as those in Example 1, to obtain an ion exchange membrane with a thickness of 73 μm as prepared in Example 2, whose total effective membrane width was 101 cm, and the widths of the regions with ion exchange capacities of 0.75 mmol / g, 0.89 mmol / g and 1.05 mmol / g were 33 cm, 30 cm and 38 cm, respectively.
[0039] Example 3
[0040] (S1) Sulfonated polyetheretherketone resins having ion exchange capacities of 1.75 mmol / g, 1.84 mmol / g, 1.99 mmol / g, 2.11 mmol / g and 2.24 mmol / g were dissolved in N,N-dimethylacetamide (DMAc) to prepare membrane slurries A3, B3, C3, D3 and E3, whose reduced viscosities were 13.1 mPa·s, 12.9 mPa·s, 13.3 mPa·s, 13.0 mPa·s and 12.8 mPa·s, respectively;
[0041] (S2) A3, B3, C3, D3 and E3 slurries are placed in turn at each hopper of the casting machine head, the knife belt gap is set to 0.40 mm, and after the resin slurry is scraped flat, it is transferred to the film drying area by the casting machine for drying and film formation, to obtain the ion exchange membrane with a thickness of 51 μm prepared in Example 3, the total effective membrane width is 100 cm, and the widths of the ion exchange capacities of 1.75 mmol / g, 1.84 mmol / g, 1.99 mmol / g, 2.11 mmol / g and 2.24 mmol / g are 25 cm, 15 cm, 14 cm, 16 cm and 30 cm respectively.
[0042] Comparative Example 1
[0043] Using slurry A1 in Example 1, an ion exchange membrane with a thickness of 49 μm (containing only a homogeneous membrane of perfluorosulfonic acid resin with an ion exchange capacity of 0.75 mmol / g) was prepared under the same conditions;
[0044] Comparative Example 2
[0045] Using slurry C1 in Example 1, an ion exchange membrane with a thickness of 48 μm (containing only a perfluorosulfonic acid resin homogeneous membrane with an ion exchange capacity of 1.05 mmol / g) was prepared under the same conditions;
[0046] Battery experiment instructions:
[0047] Experiment 1: Using the ion exchange membrane prepared in Example 1 Figure 4 (A) The reaction area dimensions shown are used for battery experiments;
[0048] Experiment 2: Using the ion exchange membrane prepared in Example 1 Figure 4 (B) The reaction area dimensions shown are used for battery experiments;
[0049] Experiment 3: Using the ion exchange membrane prepared in Example 2 Figure 5 (C) The reaction zone dimensions are shown for battery experiments;
[0050] Experiment 4: Using the ion exchange membrane prepared in Example 3 Figure 6 (D) The reaction area size shown is used for battery experiments;
[0051] Experiment 5: Using the ion exchange membrane prepared in Example 3 Figure 6 (E) The reaction area size shown is used for battery experiments;
[0052] Experiment 6: Using the ion exchange membrane prepared in Example 3 Figure 6 (F) The reaction area size shown is used for battery experiments;
[0053] Comparative Example 1 Experiment: A battery experiment was conducted using the ion exchange membrane prepared in Comparative Example 1;
[0054] Comparative Example 2 Experiment: A battery experiment was conducted using the ion exchange membrane prepared in Comparative Example 2;
[0055] The test results of the above experiments are shown in Table 1 below.
[0056] Table 1 Test results of various experimental batteries
[0057] Experiment Name Coulombic efficiency (%) Voltage efficiency (%) Energy efficiency (%) Experiment 1 96.9 84.5 81.9 Experiment 2 96.5 85.1 82.1 Experiment 3 97.9 82.5 80.8 Experiment 4 93.1 87.2 81.2 Experiment 5 96.0 86.6 83.1 Experiment 6 98.2 85.7 84.2 Comparative Example 1 Experiment 97.3 82.7 80.5 Comparative Example 2 Experiment 94.5 85.5 80.8
[0058] It can be seen from the experimental test results of Comparative Examples 1 and 2 that, in the case of the same membrane thickness, the larger the ion exchange capacity, the lower the coulomb efficiency and the higher the voltage efficiency. This is because the larger the ion exchange capacity, the enhanced ion conductivity of the corresponding ions, which will lead to a decrease in membrane surface resistance, thereby increasing voltage efficiency. At the same time, the vanadium resistance of the membrane also weakens, which reduces the coulomb efficiency. In other words, the coulomb efficiency and voltage efficiency need to be balanced to a certain extent. It can be seen from this that the ion exchange membrane prepared by the present invention can balance the coulomb efficiency and voltage efficiency to a certain extent, that is, in the area with higher reaction rate, the ion exchange capacity is increased, thereby promoting rapid ion conduction and reducing membrane surface resistance; in the area with relatively low reaction rate, the ion exchange capacity is reduced, thereby improving the vanadium resistance effect, thereby improving the comprehensive energy efficiency of the battery. In addition, different IEC component widths or their ratios are different, which will affect the comprehensive energy efficiency of the battery to a certain extent. Therefore, it is necessary to comprehensively optimize the widths or their ratios of different IEC components on the basis of experiments to achieve the highest battery performance.
[0059] It can be seen from Experiment 1 and Experiment 3 that under the same test conditions, when the IEC gradient of the membrane is close or consistent, the thicker the membrane, the higher the Coulomb efficiency of the battery, but the voltage efficiency will also decrease, resulting in a decrease in the final energy efficiency. Therefore, this also shows from another aspect that while reasonably setting the IEC gradient of the membrane reaction zone, the influence of the thickness may be considered, that is, choosing a suitable IEC gradient and thickness range.
[0060] From the data results of Experiments 4, 5 and 6, it can be seen that adjusting the gradient change amount of the IEC value in the membrane reaction zone and the IEC gradient width (corresponding to the IEC zone membrane width or its ratio) will cause a certain degree of change in the Coulomb efficiency and voltage efficiency of the membrane, thereby improving the energy efficiency of the battery. This is also the change in battery efficiency brought about by the IEC gradient decrease of the membrane body along the electrolyte flow direction.
[0061] Due to the limitations of the battery reaction zone size and test conditions of the test battery used in the present invention, the membrane and battery performance prepared in the embodiments may not necessarily achieve the optimal effect. In the actual production and application process, the appropriate ion exchange membrane IEC gradient structure can be designed or selected based on the characteristics of the battery stack structure and the operating test conditions.
[0062] It should be emphasized here that the protection scope of the present invention is not limited to the above embodiments. Any technician familiar with the technical field can make equivalent replacements or changes based on the technical solutions and inventive concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. An ion exchange membrane for a flow battery, characterized in that: In the reaction zone of the flow battery, the ion exchange capacity values of the ion exchange resins in each area on the ion exchange membrane decrease gradually or gradually along the flow direction of the electrolyte.
2. The ion exchange membrane for a flow battery according to claim 1, characterized in that: Resins of different ion exchange capacities are of the same type.
3. The ion exchange membrane for a liquid flow battery according to claim 1, characterized in that: The ion exchange membrane resin includes a cation exchange membrane resin and an anion exchange membrane resin, specifically including but not limited to perfluorosulfonic acid resin, sulfonated polyetheretherketone resin, sulfonated polyethersulfone resin, and polybenzimidazole ion exchange resin.
4. The ion exchange membrane for a flow battery according to claim 1, characterized in that: The ion exchange resin is perfluorosulfonic acid resin, and the ion exchange capacity ranges from 0.75 to 1.05 mmol / g.
5. The ion exchange membrane for a flow battery according to claim 1, characterized in that: The ion exchange resin is a sulfonated polyetheretherketone resin, and the ion exchange capacity ranges from 1.75 to 2.24 mmol / g.
6. The ion exchange membrane for a flow battery according to claim 1, characterized in that: In the membrane reaction area, the ion exchange capacity value of the ion exchange resin on the ion exchange membrane presents at least three gradient changes along the electrolyte flow direction.
7. The method for preparing an ion exchange membrane for a flow battery according to claim 6, characterized in that: The width of the transition region within the membrane reaction zone is less than 2% of the total membrane width, i.e., d 过渡n / L n <2%.
8. A method for preparing an ion exchange membrane for a flow battery, characterized in that: The following steps are involved: (S1) preparing ion exchange resin slurries with different ion exchange capacities using the same solvent; (S2) placing the above-mentioned ion exchange resin slurry in the head hopper of the casting machine in order of ion exchange capacity, and simultaneously feeding the materials in parallel through the gap of the hopper mold, and then using a scraper to scrape the resin slurry flat at the set knife belt gap, and then transferring it from the casting machine to the film drying area for drying and film formation, so as to obtain the ion exchange membrane of the present invention.
9. The method for preparing an ion exchange membrane for a flow battery according to claim 8, characterized in that: In step (S1), the viscosity of the ion exchange resin slurries with different ion exchange capacities should be the same, with a tolerance within ±5%, and there should be no gap between the resin slurries in adjacent silos.
10. An application of an ion exchange membrane for a liquid flow battery, characterized in that: Applied to all flow battery systems, especially vanadium flow battery systems.